Ruqyah Dalam Mengatasi Stres Dan Kecemasan (Studi Living Hadis Di Jam’iyyah Ruqyah Aswaja Kota Medan) - Zekrinaldi, Zekrinaldi; Datmi, Muhammad Akbar Rosyidi (UIN Sumatera Utara Medan, 2024)
This research aims to understand the concept of stress and anxiety in Islam based on the hadith in Jami'iyyah Ruqyah Aswaja, Medan City. Analyzing the implementation of ruqyah as an Islamic solution to overcome stress and anxiety in Jami'iyyah Ruqyah Aswaja, Medan City. The research method used is: Qualitative research with a living hadith approach. Data collection techniques through participant observation, in-depth interviews, and documentation. The research results show that: The concept of stress and anxiety in Islam in Jami'iyyah Ruqyah Aswaja, Medan City is understood as a mental and emotional condition that is disturbed due to various factors, including internal and external factors. The implementation of ruqyah as an Islamic solution to overcome stress and anxiety at Jami'iyyah Ruqyah Aswaja, Medan City includes reading verses from the Koran, prayer, and touching certain parts of the body. Conclusion Ruqyah is an effective Islamic solution for dealing with stress and anxiety. The implementation of ruqyah at Jami'iyyah Ruqyah Aswaja Medan City is in accordance with Islamic law and provides benefits for members who experience stress and anxiety.